2017
DOI: 10.1177/1177392817701726
|View full text |Cite
|
Sign up to set email alerts
|

Modification ofS-Adenosyl-l-Homocysteine as Inhibitor of Nonstructural Protein 5 Methyltransferase Dengue Virus Through Molecular Docking and Molecular Dynamics Simulation

Abstract: Dengue fever is still a major threat worldwide, approximately threatening two-fifths of the world’s population in tropical and subtropical countries. Nonstructural protein 5 (NS5) methyltransferase enzyme plays a vital role in the process of messenger RNA capping of dengue by transferring methyl groups from S-adenosyl-l-methionine to N7 atom of the guanine bases of RNA and the RNA ribose group of 2′OH, resulting in S-adenosyl-l-homocysteine (SAH). The modification of SAH compound was screened using molecular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 57 publications
0
5
0
2
Order By: Relevance
“…During the process of methylation, MTase converts SAM as the methyl donor into SAH [ 21 , 22 ], and this process is an important replication activity. The SAM/SAH binding site on MTase has been proposed as a potential target for anti-flavivirus agents in both DENV [ 23 ] and Zika virus (ZIKV) [ 24 ]. Thus, the binding of cordycepin to the SAM/SAH binding site on MTase may inhibit DENV RNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…During the process of methylation, MTase converts SAM as the methyl donor into SAH [ 21 , 22 ], and this process is an important replication activity. The SAM/SAH binding site on MTase has been proposed as a potential target for anti-flavivirus agents in both DENV [ 23 ] and Zika virus (ZIKV) [ 24 ]. Thus, the binding of cordycepin to the SAM/SAH binding site on MTase may inhibit DENV RNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Shanmugam and colleagues also identified, [2-(4-carbamoylpiperidin-1-yl)-2-oxoethyl] 8-(1,3-benzothiazol-2-yl) naphthalene-1-carboxylate as a potent dengue viral polymerase inhibitor by maintaining the same simulation condition from the previous study [60]. Most of the inhibitors were identified through an MD simulation against viral replication proteins, such as nonstructural protein 3 (NS3), NS5 methyltransferase, and also envelope protein (E) [58][59][60][61][62][63][64]. Currently, 18 million compounds were virtually-screened against dengue replication protein NS3, where the top five compounds have shown strong predicted binding affinity for the important catalytic residues of NS3 [65].…”
Section: Gclmentioning
confidence: 99%
“…Its potential also can be determined through the score computed by software. As a result, through years, molecular docking simulation as part of computational drug delivery has developed significantly and become a crucial part of a new compound as a potential drug [13,19]. However, the molecular docking simulation may lead to false results as the rigid receptor docking employed in molecular docking simulation is not resembling the real characteristic of the receptor.…”
Section: Molecular Docking Simulations Of Ligandmentioning
confidence: 99%
“…One example of CADD is molecular docking simulation [12]. Studies describe molecular docking simulation as a study simulation to predict the conformation and affinity of ligands with a receptor [13,14]. Through various parameters such as the binding energy of ligand-receptor and root mean square deviation (RMSD), molecular docking simulation is employed [15].…”
Section: Introductionmentioning
confidence: 99%